2005
DOI: 10.1073/pnas.0500319102
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry activates extrastriate visual cortex in human and nonhuman primates

Abstract: Humans often create and appreciate visual symmetry in their environment, and the underlying brain mechanisms have been a topic of increasing interest. Here, symmetric versus random dot stimuli produced robust functional MRI (fMRI) activity in higher-order regions of human visual cortex (especially areas V3A, V4, V7, and LO) but little activity elsewhere in brain. This fMRI response was found both with and without attention controls. Moreover, it was highly correlated with the psychophysical perception of symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
211
5
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 217 publications
(260 citation statements)
references
References 31 publications
42
211
5
2
Order By: Relevance
“…The general pattern of responses by visual areas is remarkably consistent between the data reported by Sasaki et al (2005) and the data reported here. Sasaki et al (2005) found the lowest symmetry response in V3 and the strongest in functionally localized LO.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The general pattern of responses by visual areas is remarkably consistent between the data reported by Sasaki et al (2005) and the data reported here. Sasaki et al (2005) found the lowest symmetry response in V3 and the strongest in functionally localized LO.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to Sasaki et al (2005), we observed symmetry‐related responses to begin in V3 and continue throughout visual cortex; we did not find symmetry‐specific activity in V1/V2. The general pattern of responses by visual areas is remarkably consistent between the data reported by Sasaki et al (2005) and the data reported here.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations